"Will I survive this?": A qualitative exploration of the wider impacts of the COVID-19 pandemic on the health and well-being of pregnant and parenting youth and their children in Canada - Salima Meherali; Mariam Ahmad; Amber Hussain; Amyna Ismail Rehmani; Saba Nisa; Simone Lebeuf; Sarah Munro; Chandra Ashton; Zohra S. Lassi; Ashley Vandermorris; Hasina Samji; Wendy V. Norman (BMC, 2024)
Abstract Background Pregnant and parenting youth in Canada face multiple challenges in fulfilling their parenting responsibilities while meeting their own unique needs. The COVID-19 pandemic and its associated public health restrictions exacerbated their challenges by reducing access to support networks, limiting opportunities to promote growth and well-being, and destabilizing their financial and economic standing. The impacts of the pandemic on the mental, physical, and emotional health of individuals are well-documented in the literature. However, there is limited research on how the pandemic influenced the lives, health, and well-being of pregnant and parenting youth and their children in Canada. Therefore, we aimed to examine the wider impacts (social and structural determinants that directly or indirectly impact health and well-being) of the pandemic and its implications for this population. Methods We used a constructivist grounded theory approach to explore the experiences of pregnant and parenting youth during the pandemic and how certain social determinants of health intersected to shape health outcomes and influence their ability to access services. We conducted qualitative interviews using a semi-structured interview guide over Zoom. Using grounded theory principles, we inductively analyzed the data and categorized our findings into themes. Results We recruited a total of 50 participants from different regions in Canada. The findings from the interviews were categorized into the following themes: (1) "They bear the burden alone": Struggles of pregnant and parenting youth, (2) "How will I live the next day?": Concerns and consequences arising from the pandemic, and (3) "Try to keep your mask on": Navigating healthcare services while maintaining public health guidelines. Our findings highlight the various challenges encountered by the youth during the pandemic, particularly those associated with financial and economic constraints, lack of accessible health and social services, and increased stress from parenting responsibilities. Conclusion Pregnant and parenting youth in Canada encountered various barriers while accessing health and social services, maintaining their well-being, and connecting with reliable sources of support during the pandemic. Our study findings emphasize the urgent need for adaptable and comprehensive support systems explicitly catering to the needs of pregnant and parenting youth during crises, such as the pandemic.